Palladium-catalyzed direct coupling of 2-vinylanilines and isocyanides: an efficient synthesis of 2-aminoquinolines. Issue 47 (12th October 2015) - Wang, Lijie; Ferguson, Jamie; Zeng, Fanlong
Abstract : A variety of 2-aminoquinolines were prepared in good to excellent yields. Abstract : Palladium-catalyzed oxidative coupling of 2-vinylanilines and isocyanides constitutes a direct, facile, and efficient approach to 2-aminoquinolines. The procedure, employing palladium acetate and silver carbonate, is attractive in terms of assembly efficiency, functional group tolerance, and operational simplicity. A variety of 2-aminoquinolines were prepared in good to excellent yields.